Approaches to Study Politics and Political Systems (Swarnadwar, 2024)
This article aims to provide basic concepts regarding different methods of studing political science and system. For this, the author employed descriptive as well as analytical data analysis approaches. The author used secondary sources of information, often known as the desk work approach, while providing this piece of writing. According to the study, traditional approaches to studying politics and political science include philosophical, historical, and institutional approaches, while modern approaches include sociological, economic, psychological, quantitative, simulation, system, behavioral, and Marxian approaches. However, the author briefly examines some of the traditional and modern approaches to studying political science and politics. The Traditional Approach defines Political Science as the study of state, federal, and national institutions. It investigates the formal, legal, and theoretical issues. The Modern Approach focuses on “what is actually happening in the state”. It emphasized reality and facts about politics. In this regard, the article focuses on the fundamental concepts of both methods to studying politics and political science.